(untitled) - Halgin, Richard P. (Boston, 2007)
Focused, fresh, and engaging, this text captures student interest and facilitates comprehension through the widespread use of current and highly relevant clinical case studies. The fully-revised fifth edition maintains the integrative approach to treatment using the biopsychosocial model, the emphasis on cases, and the succinct coverage that have been the foundations of the text's success. It now features a more focused approach than previous editions, with the goal of presenting only the most relevant research and clinical material.
Keywords: Psychology, Pathological,Tâm lý học, tâm thần